Single incision laparoscopic fundoplication: A systematic review of the literature - Perivoliotis, Konstantinos (World J Gastrointest Surg, 2019)
BACKGROUND: Fundoplication, was first introduced as a surgical treatment method of gastroesophageal reflux disease. Consequently, several modifications of this method have been described, whereas laparoscopic fundoplication was recently introduced. Although single incision (SI) fundoplication was considered as an alternative to the conventional laparoscopic approach, several studies reported an increased operation duration, and high rates of multiport conversion and incisional hernia. AIM: To provide a current overview of the technical variations and the postoperative outcomes of patients submitted to SI fundoplication. METHODS: The present systematic review of the literature was designed and conducted on the basis of the PRISMA guidelines. A systematic screening of the electronic scholar databases (Medline, Scopus and Web of Science) was performed. RESULTS: Literature search resulted in the identification of 19 studies. Overall, 266, 137 and 110 SI Nissen, Dor and Toupet fundoplications were reported, respectively. In the majority of the trials, standard laparoscopic instruments were used. The left liver lobe was displayed through the use of forceps, graspers, retractors, drains or even glue. Both intra-corporeal and extracorporeal suturing was described. Mean operative time was 136.3 min. Overall complication rate was 5.2% and the rate of incisional hernia was 0.9%. No mortality was reported. CONCLUSION: Due to the methodological heterogeneity and the lack of high quality studies comparing multi to single access techniques and the several variations, we conclude that further well designed studies are necessary, in order to evaluate the role of SI fundoplication.